Novel application assigned to toluquinol: inhibition of lymphangiogenesis by interfering with VEGF-C/VEGFR-3 signalling pathway - García-Caballero, Melissa; Blacher, S.; Pauper, J.; Rodríguez-Quesada, Ana María; Medina-Torres, Miguel Ángel; Noël, Agnès (Wiley, 2016)
BACKGROUND AND PURPOSE Lymphangiogenesis is an important biological process associated with the pathogenesis of several diseases, including metastatic dissemination, graft rejection, lymphoedema and other inflammatory disorders. The development of new drugs that block lymphangiogenesis has become a promising therapeutic strategy. In this study, we investigated the ability of toluquinol, a 2-methyl-hydroquinone isolated from the culture broth of the marine fungus Penicillium sp. HL-85-ALS5-R004, to inhibit lymphangiogenesis in vitro, ex vivo and in vivo. EXPERIMENTAL APPROACH We used human lymphatic endothelial cells (LECs) to analyse the effect of toluquinol in 2D and 3D in vitro cultures and in the ex vivo mouse lymphatic ring assay. For in vivo approaches, the transgenic Fli1:eGFPy1 zebrafish, mouse ear sponges and cornea models were used. Western blotting and apoptosis analyses were carried out to search for drug targets. KEY RESULTS Toluquinol inhibited LEC proliferation,migration, tubulogenesis and sprouting of new lymphatic vessels. Furthermore, toluquinol induced apoptosis of LECs after 14 h of treatment in vitro, blocked the development of the thoracic duct in zebrafish and reduced the VEGF-C-induced lymphatic vessel formation and corneal neovascularization in mice. Mechanistically, we demonstrated that this drug attenuates VEGF-C-induced VEGFR-3 phosphorylation in a dose-dependentmanner and suppresses the phosphorylation of Akt and ERK1/2. CONCLUSIONS AND IMPLICATIONS Based on these findings, we propose toluquinol as a new candidate with pharmacological potential for the treatment of lymphangiogenesis-related pathologies. Notably, its ability to suppress corneal neovascularization paves the way for applications in vascular ocular pathologies.
Keywords: Antiangiogénicos; Toluquinol; Lymphangiogenesis; VEGF-C; VEGFR-3